Industrial Boiler Performance Assessment Using Combined Heat Loss and Input–Output Efficiency Methods: A Pulverized Coal Power Plant Case Study - Surendra, Denny (Eksergi, 2026)
Reliable evaluation of boiler thermal performance is essential for improving fuel utilization and operational stability in coal-fired power plants. Although boiler efficiency is commonly assessed using either heat-loss diagnostics or input–output energy balance, few industrial studies integrate both approaches to interpret real operational behavior under steady conditions. This study presents an integrated thermodynamic and operational analysis of a large-scale pulverized coal boiler operating at a steam power plant in Jepara, Indonesia. Field operational data were obtained from the plant distributed control system during stable operation, and corresponding coal samples were laboratory-tested to determine the High Heating Value (HHV). Boiler efficiency was evaluated using both the indirect heat-loss method and the direct input–output method across seven representative datasets. The indirect analysis yields efficiencies of 88.48–89.95%, with dominant losses associated with dry flue gas sensible heat and hydrogen-related vapor formation. The direct evaluation produces efficiencies of 87.53–89.64%, confirming stable near-constant load operation with adaptive fuel control. The results indicate that efficiency variations are governed primarily by combustion stability and thermodynamic loss structure rather than fuel calorific value alone